Analysis of Digitalisation, MIS, Service Quality, Operational Efficiency on HR Performance at Bunda Sarini Clinic - Wijaya, Giovanni Owen Nanda; Yunus, Eddy (PT. Riset Press International, 2025)
This study investigates the influence of Digitalization, Management Information Systems (MIS), Service Quality, and Operational Efficiency on HR Performance at Bunda Sarini Primary Clinic in Banyuwangi. Using a quantitative research design, the study collected data through structured surveys and analyzed it using multiple regression analysis. The results indicate a strong correlation (R = 0.805) between the independent variables and HR Performance, with 64.8% of the variance (R² = 0.648) explained by these factors. The F-test (F = 15.872, Sig. = 0.000) confirms that these variables collectively exert a statistically significant impact on HR Performance. Among them, Service Quality (β = 0.389, t = 4.321, Sig. = 0.000) demonstrates the most substantial effect. The study underscores the necessity of improving service quality, advancing digitalization, and strengthening operational efficiency to enhance workforce productivity. Future research should incorporate employee engagement, leadership styles, and workplace culture to gain a more comprehensive perspective on HR Performance.